PERBANDINGAN ANTARA EKONOMI ISLAM DENGAN EKONOMI KAPITALISME - Wibawanti, Elisa; Jaharuddin, Jaharuddin (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
The greatness of the capitalist economic theory has been questioned by many economists. Because economic crises have always occurred throughout history, an alternative economic theory is needed. The aspired economic theory is an economic system that is able to create justice and mutual prosperity, accompanied by the concept of the blessing of the world and the hereafter. This is the Islamic economic theory that will bring justice and overall prosperity. The Islamic Economic System distinguishes between the discussion of economics from the point of view of the production of goods and services covered in the discussion of economics" and the discussion of economics from the point of view of the ways to obtain, to use, and to distribute goods and services covered by the discussion of the economic system". The conventional economic system makes the discussion of "economics" and "economic systems" an inseparable unit )